Are Strong Brands a Source of Competitive Advantage in the Virtual World? - Sharma, Piyush (IGI Global, 2012)
Offshore outsourcing is a fast-growing trend in the world economy today, and it is changing the way business is done across national boundaries. Specifically, customers are increasingly interacting with service employees located in other countries resulting in many instances of customer backlash due to poor perceived service quality and dissatisfaction. Prior research argues that service firms with strong brands may be less vulnerable to such negative reaction from customers. However, recent studies show that consumer ethnocentrism and unfavorable attitudes towards offshore outsourcing may adversely impact perceived service quality, satisfaction, complaint behavior, brand image, brand loyalty, and repeat purchase intentions. This chapter summarizes these diverse findings and highlights the importance of customer education and employee training to prevent the erosion of brand image and loyalty on one hand, and improve perceived service quality and customer satisfaction on the other, for companies using offshore outsourcing of customer services.